2017
DOI: 10.1093/intqhc/mzx003
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of clinical impact grading by healthcare professionals of common prescribing error and optimisation cases in critical care patients

Abstract: Representative clinical impact grades for over 100 common prescribing error and optimisation cases are reported for potential clinical practice and research application. The between professional variability highlights the importance of multidisciplinary perspectives in assessment of medication error and optimisation cases in clinical practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Some studies that did perform knowledge testing 32,36 have revealed some knowledge deficits, whereas other studies have shown that there is a significant variability between risk perceptions among health care professionals. 37,38 Administration method errors have also been reported by previous studies. 2,14,39 Nonadherence to the drug administration record protocol (i.e., documentation errors) was commonly recorded, and this is in line with findings from previous studies.…”
Section: Discussionsupporting
confidence: 72%
“…Some studies that did perform knowledge testing 32,36 have revealed some knowledge deficits, whereas other studies have shown that there is a significant variability between risk perceptions among health care professionals. 37,38 Administration method errors have also been reported by previous studies. 2,14,39 Nonadherence to the drug administration record protocol (i.e., documentation errors) was commonly recorded, and this is in line with findings from previous studies.…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, under-reporting of errors to patients and informal incident reporting systems (i.e., informal discussions with peers or supervisors) remains a significant problem in cancer care (Levinson, 2012;Olsen et al, 2007;Sari, Sheldon, Cracknell, & Turnbull, 2007). Variability in risk assessments and responses to errors may occur as a result of providers' subjective assessments (Bourne et al, 2017). The importance of gathering data from various sources, and the inclusion of multidisciplinary perspectives when assessing health care errors in clinical practice and research, has been emphasised in the literature (Bourne et al, 2017;Lipczak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Variability in risk assessments and responses to errors may occur as a result of providers' subjective assessments (Bourne et al, 2017). The importance of gathering data from various sources, and the inclusion of multidisciplinary perspectives when assessing health care errors in clinical practice and research, has been emphasised in the literature (Bourne et al, 2017;Lipczak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Clinical impact gradings of critical care pharmacist activity in terms of error intercepts and optimisation activity have been verified by a 30-strong multi-professional panel. 18 Pharmacist's activity can generally be grouped into three broad areas. 13 First, the pharmacist's independent review occurs when reviewing charts, clinical data, performing medicines reconciliation, etc.…”
Section: Current Impact In Critical Carementioning
confidence: 99%
“…1517 Clinical impact gradings of critical care pharmacist activity in terms of error intercepts and optimisation activity have been verified by a 30-strong multi-professional panel. 18…”
Section: Current Impact In Critical Carementioning
confidence: 99%